Local loss and spatial homogenization of plant diversity reduce ecosystem multifunctionality. Issue 1 (January 2018) - Hautier, Yann; Isbell, Forest; Borer, Elizabeth; Seabloom, Eric; Harpole, W.; Lind, Eric; MacDougall, Andrew; Stevens, Carly; Adler, Peter; Alberti, Juan; Bakker, Jonathan; Brudvig, Lars; et al.
Abstract Biodiversity is declining in many local communities while also becoming increasingly homogenized across space. Experiments show that local plant species loss reduces ecosystem functioning and services, but the role of spatial homogenization of community composition and the potential interaction between diversity at different scales in maintaining ecosystem functioning remains unclear, especially when many functions are considered (ecosystem multifunctionality). We present an analysis of eight ecosystem functions measured in 65 grasslands worldwide. We find that more diverse grasslands—those with both species-rich local communities (α-diversity) and large compositional differences among localities (β-diversity)—had higher levels of multifunctionality. Moreover, α- and β-diversity synergistically affected multifunctionality, with higher levels of diversity at one scale amplifying the contribution to ecological functions at the other scale. The identity of species influencing ecosystem functioning differed among functions and across local communities, explaining why more diverse grasslands maintained greater functionality when more functions and localities were considered. These results were robust to variation in environmental drivers. Our findings reveal that plant diversity, at both local and landscape scales, contributes to the maintenance of multiple ecosystem services provided by grasslands. Preserving ecosystem functioning therefore requires conservation of biodiversity both within and among ecological communities. Analysis of 65 grasslands worldwide from the Nutrient Network experiment reveals that plant communities with higher α- and β-diversity have higher levels of ecosystem multifunctionality, and that this effect is amplified across scales.